KARAKTERISASI BIOKIMIA BAKTERI SELULOLITIK DARI KAYU LAPUK MANGROVE DI SUNGAILIAT DAN TUKAK SADAI, PULAU BANGKA - Ardiansyah Kurniawan; Asep Awaludin Prihanto; Suci Puspita Sari; Andi Kurniawan; Euis Asriani; Abu Bakar Sambah (Jurnal Sumberdaya Akuatik Indopasifik, 2018)
Acceleration of wood weathering in the mangrove area is possible with the role of cellulolytic bacteria. Cellulolytic bacteria producing cellulase enzymes are needed by the animal feed and agriculture industries. Mangroves in Muntok Subdistrict undergo a process of adaptation to environmental changes due to tin mining, including microorganisms. Exploration of new species and strains of cellulolytic bacteria in miningaffected mangroves is needed to enrich the collection and its potential use for human needs. This study aims to identify cellulolytic bacteria in mangrove weathered wood in Muntok District, West Bangka Regency through isolation, screening, and biochemical characterization. Three sampling locations, namely Sukal Mangrove, Peltim Mangrove, and Tembelok Mangrove result 22 bacterial isolates with 11 isolates showing the ability of cellulose degradation in qualitative tests using Lugol. The biochemical characterization of bacterial isolates with the greatest cellulose degradation was directed towards Citrobacter freundii and Vibrio alginolyticus in samples of Sukal Mangrove and Actinomyces bovis in isolates from Peltim Mangrove.